Analysis of seismic performance of gravity dam based on ultra-high performance concrete reinforcement. Issue 1 (August 2020) - Shi, Junfei; Ma, Tianxiao; Gao, Lingang
Abstract: Damage and crack of gravity dams under earthquakes directly affect the dam's safety. Ultra-high performance concrete has high strength and durability. Whether to replace steel bars for seismic reinforcement becomes the focus of consideration. In the paper, the plastic damage model of ultra-high-performance concrete is established. Taking the gravity dam section as an example, referring to the design concept of the "gold coated silver" gravity dam, three different forms of seismic-reinforced schemes of ultra-high-performance concrete in weak areas of the dam are presented and analyze damage time histories. The calculation results show that the application of ultra-high performance concrete for reinforcement can greatly reduce the damage of the dam and improve the seismic performance of the dam. The study suggests that proper reinforcement measure can be taken according to the conditions of dams.